APPLICATION OF TRANSDUCTORS IN SHORT-CIRCUIT CURRENT MEASURING DEVICES - Nikolay I. Tsygulev; Vladimir R. Prous (Advanced Engineering Research)
The statement that transductors with magnetodielectric carbonyl iron dust-based magnetic circuits have the linear gain characteristic on the peak values throughout the full range of the real current value shift is proved in theory and by experiment. Functional scheme features of the linear periodic component short-circuit current meter are considered.